The free/open source software movement: resistance or change? - Georgopoulou, Panayiota (2009)
At a time when private companies are inventing methods of “locking information” and when neo-liberal governments are imposing strict sanctions on those who violate intellectual property rights, the Free/Open Source Software (FOSS) movement has been countering neo-liberalism and general privatization: it defies ownership regulations in a key area of growth in contemporary capitalistic societies, namely, the construction and use of information. At the end of the ‘90s, FOSS seemed to be a disruptive and destabilizing force in terms of intellectual property and neoliberalism, yet as open software, it has evolved into a singular economic phenomenon indicating that commercialization and financial gain can now exist without being based on the notion of ownership. This may not be detrimental to capitalistic logic, but broaden its prospects. By negating the ownership regime imposed on information and putting the historical potential of the “economy of abundance” of the new digital world to good use, is FOSS then laying down a plan for political resistance or showing the way towards a potential transformation of capitalism? Perhaps the new conditions of politics can be found in the heart of economy and in its transition towards an “economy of abundance” in the digital world. Keywords: Copyright; Free information; Community; Free/Open Source Software; Economy of abundance